MINERALOGICAL AND GEOCHEMICAL ASSESSMENT OF PARTICULATE MATTER (PM10) IN IBADAN METROPOLIS, NIGERIA (2015)
Particulate Matter (PM) are suspended solid and liquid particles in the atmosphere, classified into coarse (PM10, 2.5 to 10μm) and fine (PM2.5 <2.5μm) particles. Particulate Matter has been reported to have negative impact on the climate, human health and ecosystems. Previous works in Ibadan had focussed on occurrences and concentrations of PM10 without adequate attention to mineralogical and elemental composition. This study was designed to investigate the mineralogical and elemental composition of PM10 in Ibadan metropolis in order to ascertain their sources and potential hazards to human health. Two hundred and five suspended PM10 samples were purposively collected from Traffic Area (TA) (40), Industrial Areas (IA) (40), Dumpsite/Incinerator (DI) (40) and Residential Area (RA) (85) using high volume air sampler with cellulose filter. The samples were collected in both dry and rainy seasons from February to December, 2011. Rocks (12), soils (25) and deposited dusts (30) within the metropolis were also sampled. The morphology and mineralogy of the PM10, rocks and soils were determined using Scanning Electron Microscopy/Energy Dispersive Spectroscopy and X-ray Diffractometry while the elemental compositions were determined using inductively coupled plasma optical emission spectrometry. The results of PM10 concentration were compared with World Health Organization (WHO), United State Environmental Protection Agency (USEPA) and National Environmental Standards and Regulation Enforcement Agency (NESREA) standards. Data were analysed using descriptive statistic and Principal Component Analysis (PCA). Minimum (32.2 μg/m3) and maximum (627.6 μg/m3) concentrations of PM10 were observed at the peak of the rainy and dry seasons respectively; with daily average concentration of 652.1μg/m3, 377.5 μg/m3, 285.7 μg/m3 and 214.8 μg/m3 for IA, TA, DI and RA respectively. All daily average concentrations exceeded WHO, USEPA and NESREA standards. The morphology of the individual PM10 particle are mostly coarse (>2.5 μm) and irregular in shape with very few being regular and fine (<2.5 μm); an indication of the localised nature of the PM10 particles. The minerals in the PM10 particles are mostly chlorite, illite, kaolinite, smectite, quartz, feldspar, mica and amphibole. Quartz, feldspar, mica and amphibole were the dominant minerals in the rock units while kaolinite and illite were dominant in the soils. The elemental concentrations in the PM10, soils and deposited dusts UNIVERSITY OF IBADAN LIBRARY iii follow the order Ca>Fe>Al>Na>Mg>Si>Zn>Cu>Mo>Mn>Ba>Ti>Pb>Ni>La. The IA showed highest average concentration of all elements in the PM10 except Ba, which was highest in TA. The elemental composition agreed with the mineralogical data as revealed by the PCA. Factor 1 was loaded with Al, Si, Ca, Fe and Mg while Factor 2 was Ca, Mg, and Na, indicating crustal source for these elements. Factor 3 was loaded with Pb, Zn, indicating industrial emission source while Factors 4 (Cu, La, Mo) and 5 (Ba, Mn) indicated traffic related contribution. The mineralogy and elemental composition in the Particulate Matter (PM10) were derived mainly from crustal sources with subordinate contributions from anthropogenic sources. The presence of Pb, Cu, Zn and Si in the coarse particulate matter could pose serious health hazard to the human population. Keywords: Particulate matter, Crustal sources, Principal component analysis, Anthropogenic sources Word count: 492